Effect of Feeding Canola Oil and Vitamin A on the Fatty Acid Profile of Egg Yolks in Laying Hens - Ahmad, Shakeel; Ahsan-ul-Haq,; Yousaf, Muhammad; Nawaz, Haq (Pakistan Journal of Nutrition, 2010)
Two hundred and forty White Leghorn laying hens at 48th week of age were randomly divided into 24 experimental units. These experimental units were allotted to eight treatment groups which were fed diets with 0, 2, 3 and 4% canola oil with 3000 or 10000 IU vitamin A/kg of diet (4 x 2 factorial design), for a period of 12 weeks in order to observe the effects of feeding canola oil and vitamin A on the fatty acid profile of egg yolks. Two eggs per replicate were collected at the end of trial and analyzed for fatty acid contents of egg yolks. The increase in dietary canola oil levels increased (p0.05) the egg yolk fatty acid composition.